2021
DOI: 10.3390/diagnostics11081346
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Epigenetic Role and Clinical Impact of Histone Deacetylases in Neoplasia

Abstract: Histone deacetylases (HDACs) have long been implicated in tumorigenesis and tumor progression demonstrating their important participation in neoplasia. Therefore, numerous studies have been performed, highlighting the mechanism of HDACs action in tumor cells and demonstrating the potential role of HDAC inhibitors in the treatment of different cancer types. The outcome of these studies further delineated and strengthened the solid role that HDACs and epigenetic modifications exert in neoplasia. These results ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Class IIb HDACs (HDAC-6 and -10), have a duplication of their catalytic domains, whereas HDAC-6 is the only deacetylase known to act on tubulin, which is required for disposal of misfolded proteins in aggresomes [ 1 ]. HDAC proteins, and especially the most thoroughly investigated members of class I, have been recently shown to be overexpressed in a plethora of human malignancies, being associated also with tumorigenesis, disease progression, and prognosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Class IIb HDACs (HDAC-6 and -10), have a duplication of their catalytic domains, whereas HDAC-6 is the only deacetylase known to act on tubulin, which is required for disposal of misfolded proteins in aggresomes [ 1 ]. HDAC proteins, and especially the most thoroughly investigated members of class I, have been recently shown to be overexpressed in a plethora of human malignancies, being associated also with tumorigenesis, disease progression, and prognosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive activity of HDAC could facilitate the deacetylation of histones, causing down-regulation of the expression of tumour suppressor genes. Molecules that inhibit the activity of HDAC have been evaluated as a possible antitumour therapy in both humans and dogs (reviewed by Xavier et al, 2020 and Goutas et al, 2021 [ 177 , 178 ]). It is thought that HDAC inhibitors (HDACi) induce the acetylation of deacetylated histones, thereby promoting the expression of tumour suppressor genes, which could result in an antitumour effect [ 179 ].…”
Section: Therapies For Ucmentioning
confidence: 99%
“…Histone proteins represent dynamic components of the chromatin structure and play a critical role in the regulation of gene transcription by modification of the chromatin accessibility to the transcription machinery. Histone acetylation consists in the addition of an acetyl group to histone proteins to the lysine residues within the N-terminal tail, catalyzed by enzymes known as histone acetyltransferases (HATs) [ 14 ]. The acetylation of histones at specific positions (H3K9 residues, which mean at lysine 9 of histone 3, for example) leads to a transcriptionally active chromatin structure (euchromatin), due to the neutralization of the positive charge by the acetylation of lysine residues, diminishing their ability to bind with the negatively charged DNA [ 15 ].…”
Section: Overview Of Epigenetic Alterations In Cancermentioning
confidence: 99%
“…Several correlative data have shown that HDACs are often overexpressed in various type of cancers, conferring a poor prognosis [ 14 ]. In addition, HDACs can be aberrantly recruited at specific gene promoters by oncogenic fusion proteins that drive leukaemogenesis.…”
Section: Overview Of Epigenetic Alterations In Cancermentioning
confidence: 99%